Vowel Change Found in Geoffrey Chaucers The House of Fame: Great Vowel Shift - Tia Xenia (Universitas Sanata Dharma, 2015)
It has already been understood that Great Vowel Shift (GVS) takes the major differences between the pronunciation in Middle English and Modern English. GVS is a change in pronunciation of vowel sounds in English language. The evidence of this change can be attained through written texts. It can be found by comparing Geoffrey Chaucers literary works to William Shakespeares works to see the differences. However, in this paper I focused only on analyzing the GVS in Geoffrey Chaucers poem entitled The house of Fame. The purpose of this study is to find out what kind of sound shift appears in The House of Fame and to explain in what phonological environment the vowel shift takes place. The result shows that there are seven kinds of sound shifts found in the poem. Those are [e:][i:], [i:][a?], [?:][o:], [?:][e:], [a:] [?:] [e?], [o:] [u:], and [u:] [au]. Besides, from this study, it can be concluded that there are three kinds of phonological environments employed in vowel shift.Keywords: Great Vowel Shift, Geoffrey Chaucer